THE INFLUENCE OF MIGRATION AND SOCIO-ECONOMIC DEMOGRAPHIC FACTORS ON FERTILITY IN DKI JAKARTA - Nasrullah Nasrullah (Pusbindiklat - LIPI, 2013)
The development progress and changes in various sectors precede to the population movements. Subsequently, changes in the population movement (migration) and socio-economic demographic factors in the society will consign an influence on changing patterns and behavioural fertility. This study aims to examine the influence of migration and socio-economic and demographic factors on fertility in DKI Jakarta. The analysis is conducted by using Multinomial Logistic Regression method. The results found that migrants have higher tendency than non migrants to have 2-3 children while non migrants have higher tendency than migrants to have 1 or 4 or more children. It is also found that migration significantly influences fertility of women to have four or more children. Migrants are less likely (0.76 times) than non migrants to have four or more children than to have no children. On the other hand, it is found that there is influence of socio-economic and demographic factors on fertility.